THE DISCOURSE OF EXISTENTIALISM: A CRITICAL DISCOURSE ANALYSIS OF FREEDOM, RESPONSIBILITY, AND BAD FAITH IN SARTRE'S NO EXIT (Contemporary Journal of Social Science Review, 2025)
This research looks at No Exit (1944) by Jean-Paul Sartre from the perspective of Critical Discourse Analysis (CDA), especially using the model offered by Norman Fairclough. The analysis includes how language in No Exit existentialistically captures themes of freedom, responsibility, and bad faith, focusing on the relations of power and the social structures on which they are built. All of these existential concepts are vital to Sartre's philosophy, which are framed within the interactions of the three characters Garcin, Inez, and Estelle that are confined in a room and made to face the ramifications of their actions. This study seeks to use CDA to interrogate the ability of the characters' dialogues to mask deeper social and ideological manifestations that underlie the speech acts since language is fundamentally a tool of not only communication but also control and self-deception. This study seeks to understand language and communication in the context of the social relations and power structures that exists around them. The study examines how the dialogues of No Exit reflect the fundamental linguistic and rhetorical properties of speech acts connected with the theme of bad faith while exploring the construct of the power framework within the characters’ hierarchical social relations. It analyzes how the character’s grapple with issues of liberty and responsibility, using language as their primary means of mediating the conflict. The research analyzes about the dove tailing of the character’s language and bad faith self-deception, denial and other phenomena exposing self-ideology. Focusing on discourse, power, and existential philosophy, this study broadens the mechanisms of how Sartre’s existential themes are exercised through characters’ language. This research helps the reader to better understand No Exit by showing that Sartre’s philosophy is not only an idea, but something that is built and sustained through the speech of the characters. Through CDA, it illustrates how language is used as a tool for existential self-deception and power relations in society. This study adds on what other researchers have done on Sartre by uniting existential philosophy with discourse analysis, adding and intersectional sociological and existential perspective of human freedom, responsibility, and identity.